Structural Basis of Arp2/3 Complex Inhibition by GMF, Coronin, and Arpin. Issue 2 (20th January 2017) - Sokolova, Olga S.; Chemeris, Angelina; Guo, Siyang; Alioto, Salvatore L.; Gandhi, Meghal; Padrick, Shae; Pechnikova, Evgeniya; David, Violaine; Gautreau, Alexis; Goode, Bruce L.
Abstract: The evolutionarily conserved Arp2/3 complex plays a central role in nucleating the branched actin filament arrays that drive cell migration, endocytosis, and other processes. To better understand Arp2/3 complex regulation, we used single-particle electron microscopy to compare the structures of Arp2/3 complex bound to three different inhibitory ligands: glia maturation factor (GMF), Coronin, and Arpin. Although the three inhibitors have distinct binding sites on Arp2/3 complex, they each induced an "open" nucleation-inactive conformation. Coronin promoted a standard (previously described) open conformation of Arp2/3 complex, with the N-terminal β-propeller domain of Coronin positioned near the p35/ARPC2 subunit of Arp2/3 complex. GMF induced two distinct open conformations of Arp2/3 complex, which correlated with the two suggested binding sites for GMF. Furthermore, GMF synergized with Coronin in inhibiting actin nucleation by Arp2/3 complex. Arpin, which uses VCA-related acidic (A) motifs to interact with the Arp2/3 complex, induced the standard open conformation, and two new masses appeared at positions near Arp2 and Arp3. Furthermore, Arpin showed additive inhibitory effects on Arp2/3 complex with Coronin and GMF. Together, these data suggest that Arp2/3 complex conformation is highly polymorphic and that its activities can be controlled combinatorially by different inhibitory ligands. Graphical Abstract: Highlights: Coronin, GMF, and Arpin each induce related open conformations in Arp2/3 complex. GMF binding induces two distinct inhibitory states of Arp2/3 complex. Coronin, GMF, and Arpin combinatorially inhibit Arp2/3 complex activity. Arpin has two separate binding sites on Arp2/3 complex Arp2 and Arp3.